Usury and Economic Ethics: Al-Faruqi's Approach to Justice - Trisna Dwi Nur Rodhiyah; Ahmad Virman Haris; Helmi Syaifuddin (al-Afkar, Journal For Islamic Studies, 2026)
This discussion highlights the problem of riba in the context of modern economics and offers solutions based on the principles of Islamic sociology of economics. Riba is considered a major obstacle to achieving social justice and economic well-being. Therefore, it is important to understand concepts such as zakat, sadaqah, and social responsibility in building a sustainable economic system. By implementing Islamic financial instruments, such as mudaraba and musharakah, communities can avoid riba practices and create more equitable alternatives. nnFurthermore, community-based economic development and community empowerment through zakat and sadaqah are the main focuses in poverty alleviation. Through cooperation and ethical business practices, it is hoped that economic challenges can be overcome, and shared prosperity can be improved. This comprehensive approach not only creates a just economic system, but also builds social awareness that is important in every financial transaction, in accordance with Islamic values.